PENGARUH PEMASARAN DIGITAL DAN PENGALAMAN PELANGGAN TERHADAP LOYALITAS PELANGGAN ALFAMART TB SIMATUPANG 9 JAKARTA TIMUR - Amirul Mu'minin; Nino Nopriandi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The research to analyze the influence of digital marketing and and customer experience on customer loyalty at Alfamart Tb Simatupang 9 Jakarta Timur. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all customers at Alfamart TB Simatupang 9 within three months. The sampling technique uses simple random sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the digital marketing and customer experience have a positive and significant on customer loyalty at Alfamart Tb Simatupang 9 Jakarta Timur.